Searching for the spirit of enterprise : - Farrell, Larry C. (Dutton, 1993)
Contents: Big trouble at big business; sense of mission: Creating high purpose and high standards; Customer/Product vision: My customer, my product, my self-respect; High-speed Innovation: The necessity to invent and the freedom to act; Self - inspired behavior: ordinary people doing extraorinary things; transforming bureaucracy to enterprise: dismantling the twentieth-century corporation; Epilogue: The enterprise of nations...